A Systematic Investigation of Assessment Scores, Self-Efficacy, and Clinical Practice: Are They Related? - Katie Stringer Lucero; Donald E. Moore (Taylor & Francis Group, 2024)
A considerable amount of continuing professional development (CPD) for health professionals is online and voluntary. There is evidence that some CPD activities impact clinical practice outcomes from self-reported and objective, administrative data. Some studies have shown that there is a potential mediating effect of knowledge/competency and/or self-efficacy between participation in CPD activities and the outcomes of that participation, specifically clinical practice. However, because clinical practice in those studies has been self-report, little is known about how this relationship impacts real world clinical practice. The purpose of the current study is to examine the relationship between knowledge/competency, self-efficacy, and real-world clinical practice so that we can begin to understand whether our focus on knowledge/competency and self-efficacy to change real-world clinical practice is empirically supported. We employed secondary data analysis from pre-participation questionnaire and medical and pharmacy claims data originally collected in three evaluations of online CPD interventions to examine if the relationship between knowledge/competency and self-efficacy contributed to physicians' real-world clinical practice. Results show an association between knowledge/competency scores and ratings of self-efficacy and suggest unique contributions of knowledge/competency and self-efficacy to clinical practice. Study results support the value of knowledge/competency scores and self-efficacy ratings as predictors of clinical practice. The effect size was larger for self-efficacy suggesting it may be a more practical indicator of clinical practice for CPD evaluators because its process of question development is simpler than the process for knowledge and case-based decision-making questions. However, it is important to conduct thorough need assessments which may include knowledge/competency assessments to identify topics to cover in CPD activities that are more likely to increase self-efficacy and ultimately, clinical practice.